Sphaeraphodius gaohani, a new genus and species of Aphodiini (Coleoptera: Scarabaeidae: Aphodiinae) from Guangxi, China - Kakizoe, Showtaro; Jiang, Ri-Xin; Cai, Hao-Hong; Wang, Shuo (Zootaxa, 2021)
Sphaeraphodius gaohani Kakizoe, Jiang & Wang, a new genus and new species of the tribe Aphodiini, is described based on two female specimens from Guangxi, China. This new genus differs considerably from any previously known genera of Aphodiini by dorsally swollen body covered by considerably long setae, and lack of transverse setiferous carinae on outer surfaces of meso- and metatibiae. This new taxon is found sympatrically with the termite Macrotermes sp. in the field. Therefore, this species is perhaps termitophilous, but we cannot conclude it at this time due to the insufficient information available in the field.